Thermoionic Vacuum Arc (TVA) - one of the best suitable method for high purity compact smooth thin films deposition - Ehrich, H.; Musa, G.; Mustata, I. (Вопросы атомной науки и техники, 2002)
Описан метод термоионной вакуумной дуги (ТВД) как новый наиболее подходящий метод для осаждения тонких пленок высокой чистоты с компактной структурой и очень гладких, удобный для получения пленок с наноструктурой. ТВД может производить источник плазмы чистых металлов внутри вакуумной камеры (включая высоковольтные условия), обеспечивая эффективную ионную бомбардировку наносимой пленки атомами напыляемого материала. Энергия ионов полностью контролируется и даже может изменяться в течение осаждения. Описана также возможность нанесения тонких пленок углерода, эти пленки полностью свободны от водорода. Описаний метод термойонної вакуумної дуги (ТВД) як новий найбільш придатний метод для осадження тонких плівок високої чистоти з компактною структурою та дуже гладких, який зручний для отримання плівок із наноструктурою. ТВД може генерувати джерело плазми чистих металів всередині вакуумної камери (включаючи високовольтні умови), забезпечуючи ефективне іонне бомбардування плівки, що наноситься, атомами матеріалу, який наноситься. Енергія іонів повністю контролюється і навіть може змінюватися протягом осадження. Описана також можливість нанесення тонких плівок вуглецю, ці плівки цілком вільні від водню. Thermionic Vacuum Arc (TVA) is described as a new very suitable for deposition of high purity thin films with compact structure and extremely smooth, just convenient for nanostructure film realization. TVA can generate pure metal vapor plasma source inside of a vacuumed vessel (including H. V. conditions), ensuring energetic ions bombardment of the just depositing material own atoms of the condensing film. The energy of ions can be fully controlled and changed even during deposition. Possibility of condense the carbon thin films is also described, these films being completely hydrogen free.